Resource Use and Its Ecological Implications: A Case Study of Tinau Watershed - Shrestha, Vinod (Himalayan Review, 2011)
Not available. Key words: Ecological Implications; Tinau Watershed; Developing countries The Himalayan Review Nepal Geographical Society Vol. XVII-XIX 1986-1988 Page:63-76 Uploaded date: 2 June, 2011